Importance of the biofilm matrix for the erosion stability of Bacillus subtilis NCIB 3610 biofilms. Issue 20 (11th April 2019) - Klotz, M.; Kretschmer, M.; Goetz, A.; Ezendam, S.; Lieleg, O.; Opitz, M.
Abstract : Erosion of bacterial biofilms is dependent on the composition of the biofilm matrix and the surrounding chemical environment. Abstract : Production and secretion of biomolecules can provide new emergent functionalities to the synthesizing organism. In particular, the secretion of extracellular polymeric substances (EPS) by biofilm forming bacteria creates a biofilm matrix that protects the individual bacteria within the biofilm from external stressors such as antibiotics, chemicals and shear flow. Although the main matrix components of biofilms formed by Bacillus subtilis are known, it remains unclear how these matrix components contribute to the erosion stability of B. subtilis biofilms. Here, we combine different biophysical techniques to assess this relation. In particular, we quantify the importance of specific biofilm matrix components on the erosion behavior of biofilms formed by the well-studied Bacillus subtilis NCIB 3610. We find that the absence of biofilm matrix components decreases the erosion stability of NCIB 3610 biofilms in water, largely by abolishing the hydrophobic surface properties of the biofilm and by reducing the biofilm stiffness. However, the erosion resistance of NCIB 3610 biofilms is strongly increased in the presence of metal ions or the antibiotic ciprofloxacin. In the first case, unspecific ionic cross-linking of biofilm components or individual bacteria seems to be responsible for the observed effect, and in the second case there seems to be an unspecific interaction between the antibiotic and the biofilm matrix. Taken together, our results emphasize the importance of the biofilm matrix to reduce biofilm erosion and give insights into how the specific biomolecules interact with certain chemicals to fulfill this task.